Condensation sink of atmospheric vapors: the effect of vapor properties and the resulting uncertainties. Issue 7 (11th October 2021) - Tuovinen, Santeri; Kontkanen, Jenni; Cai, Runlong; Kulmala, Markku
Abstract : The condensation sink depends on vapor properties and thus inaccurate assumptions about them can lead to uncertainties in the descriptions of vapor mass balance or cluster formation. Abstract : Aerosol particles affect the climate and human health. Thus, understanding and accurately quantifying the processes associated with secondary formation of aerosol particles is highly important. The loss rate of vapor to aerosol particles affects the mass balance of that vapor in the atmosphere. The condensation sink (CS) describes the condensation rate of vapor to particles while the effective condensation sink (CSeff ) describes the loss rate including both condensation and evaporation of vapor. When the CS is determined, the mass accommodation coefficient ( α ) is usually assumed to be unity and the condensing vapor is often assumed to be sulfuric acid. In addition, evaporation is assumed to be negligible (CSeff = CS) and the total loss rate of vapor is described by the CS. To study the possible uncertainties resulting from these assumptions, we investigate how vapor properties such as vapor mass and α affect the CS. In addition, the influence of evaporation on the CSeff is evaluated. The CS and CSeff are determined using particle number size distribution data from Beijing, China. Vapors are observed to have differing CSs depending on molecular mass and diffusivity volume and larger molecules are lost at a slower rate. If the condensing vapor is composed, for example, of oxidized organic molecules, which often have larger masses than sulfuric acid molecules, the CS is smaller than for pure sulfuric acid vapor. We find that if α is smaller than unity, the CS can be significantly overestimated if unity is assumed. Evaporation can significantly influence the CSeff for volatile and semi-volatile vapors. Neglecting the evaporation may result in an overestimation of vapor loss rate and hence an underestimation of the fraction of vapor molecules that is left to form clusters.